Unveiling the unseen: Photovoice advocacy on sexual violence in schools - Sulaeman, Sofia Farzanah; Fitri, Susi; Marjo, Happy Karlina (KONSELI: Jurnal Bimbingan dan Konseling (E-Journal), 2025)
This study aims to examine the effectiveness of employing the photovoice method within the framework of Participatory Action Research (PAR) to enhance senior high school students’ awareness of the dangers of sexual violence in educational settings. Through a participatory approach involving photography, narrative construction, and group discussion, students were encouraged to identify various forms of sexual violence, understand the underlying contributing factors, and formulate prevention strategies relevant to their school context. The findings indicate that photovoice is not only effective as an educational medium but also strengthens students’ active engagement, fosters spaces for critical reflection, and promotes the development of an open and inclusive dialogical culture within schools. The implications of this study highlight the importance of synergy among educational practices, school policies, and psychosocial support services in creating a safe learning environment. Although this research is limited to a specific school context with a relatively small number of participants, the results provide valuable contributions to the development of school counseling programs, educational policy, and future studies with broader scope.